Late follicular phase progesterone elevation during ovarian stimulation is not associated with decreased implantation of chromosomally screened embryos in thaw cycles. Issue 8 (10th July 2020) - Hernandez-Nieto, Carlos; Lee, Joseph A; Alkon-Meadows, Tamar; Luna-Rojas, Martha; Mukherjee, Tanmoy; Copperman, Alan B; Sandler, Benjamin
Abstract: STUDY QUESTION: What is the impact of a late follicular phase progesterone elevation (LFPE) during controlled ovarian hyperstimulation (COH) on embryonic competence and reproductive potential in thaw cycles of preimplantation genetic testing for aneuploidy (PGT-A) screened embryos? SUMMARY ANSWER: Our study findings suggest that LFPE, utilizing a progesterone cutoff value of 2.0 ng/ml, is neither associated with impaired embryonic development, increased rate of embryonic aneuploidy, nor compromised implantation and pregnancy outcomes following a euploid frozen embryo transfer (FET) cycle. WHAT IS KNOWN ALREADY: Premature progesterone elevation during COH has been associated with lower pregnancy rates due to altered endometrial receptivity in fresh IVF cycles. Also, increased levels of progesterone (P) have been suggested to be a marker for ovarian dysfunction, with some evidence to show an association between LFPE and suboptimal embryonic development. However, the effect of LFPE on embryonic competence is still controversial. STUDY DESIGN, SIZE, DURATION: Retrospective cohort analysis in a single, academic ART center from September 2016 to March 2020. In total, 5244 COH cycles for IVF/PGT-A were analyzed, of those 5141 were included in the analysis. A total of 23 991 blastocysts underwent trophectoderm biopsy and PGT analysis. Additionally, the clinical IVF outcomes of 5806 single euploid FET cycles were evaluated. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cohorts were separated in two groups: Group 1: oocytes retrieved from cycles with normal P levels during ovulation trigger (P ≤ 2.0 ng/ml); Group 2: oocytes retrieved after cycles in which LFPE was noted (P > 2.0 ng/ml). Extended culture and PGT-A was performed. Secondly, IVF outcomes after a single euploid FET were evaluated for each cohort. MAIN RESULTS AND THE ROLE OF CHANCE: Four thousand nine hundred and twenty-five cycles in Group 1 were compared with 216 cycles on Group 2. Oocyte maturity rates, fertilization rates and blastulation rates were comparable among groups. A 65.3% ( n  = 22 654) rate of utilizable blastocysts was found in patients with normal P levels and were comparable to the 62.4% ( n  = 1337) observed in those with LFPE ( P  = 0.19). The euploidy rates were 52.8% ( n  = 11 964) and 53.4% ( n  = 714), respectively, albeit this difference was not statistically significant ( P  = 0.81). Our multivariate analysis was fitted with a generalized estimating equation (GEE) and no association was found with LFPE and an increased odds of embryo aneuploidy (adjusted odds ratio 1.04 95% CI 0.86–1.27, P  = 0.62). A sub-analysis of subsequent 5806 euploid FET cycles (normal P: n  = 5617 cycles and elevated P: n  = 189 cycles) showed no differences among groups in patient's BMI, Anti-Müllerian hormone (AMH), endometrial thickness at FET and number of prior IVF cycles. However, a significant difference was found in patient's age and oocyte age. The number of good quality embryos transferred, implantation rate, clinical pregnancy rate, ongoing pregnancy rate, multiple pregnancy rate and clinical pregnancy loss rates were comparable among groups. Of the registered live births (normal P group: n  = 2198; elevated P group: n  = 52), there were no significant differences in gestational age weeks (39.0 ± 1.89 versus 39.24 ± 1.53, P  = 0.25) and birth weight (3317 ± 571.9 versus 3 266 ± 455.8 g, P  = 0.26) at delivery, respectively. LIMITATIONS, REASONS FOR CAUTION: The retrospective nature of the study and probable variability in the study center's laboratory protocol(s), selected progesterone cutoff value and progesterone assay techniques compared to other ART centers may limit the external validity of our findings. WIDER IMPLICATIONS OF THE FINDINGS: Based on robust sequencing data from a large cohort of embryos, we conclude that premature P elevation during IVF stimulation does not predict embryonic competence. Our study results show that LFPE is neither associated with impaired embryonic development nor increased rates of aneuploidy. Embryos obtained from cycles with LFPE can be selected for transfer, and patients can be reassured that the odds of achieving a healthy pregnancy are similar to the embryos exposed during COH cycles to physiologically normal P levels. STUDY FUNDING/COMPETING INTEREST(S): No funding was received for the realization of this study. Dr A.B.C. is advisor and/or board member of Sema 4 (Stakeholder in data), Progyny and Celmatix. The other authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: NA